2018
DOI: 10.1097/ncq.0000000000000291
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High-Reliability Education on Adverse Event Reporting by Registered Nurses

Abstract: Adverse event reporting is one strategy to identify risks and improve patient safety, but, historically, adverse events are underreported by registered nurses (RNs) because of fear of retribution and blame. A program was provided on high reliability to examine whether education would impact RNs' willingness to report adverse events. Although the findings were not statistically significant, they demonstrated a positive impact on adverse event reporting and support the need to create a culture of high reliabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 10 publications
0
30
0
1
Order By: Relevance
“…9 Researchers found a clinically significant increase in the number of event reports in the 6-month period after nurses received a high reliability educational program, indicating an increase in the HRO principle preoccupation with failure. 10 Limited research to date compares manifestations of HRO among hospital units with high and low safety performance. This type of research can provide a basis for translating theoretical HRO principles into clinical and administrative practice, furthering the pursuit of HRO in health care and achieving the aim of delivering safe, high-quality care.…”
mentioning
confidence: 99%
“…9 Researchers found a clinically significant increase in the number of event reports in the 6-month period after nurses received a high reliability educational program, indicating an increase in the HRO principle preoccupation with failure. 10 Limited research to date compares manifestations of HRO among hospital units with high and low safety performance. This type of research can provide a basis for translating theoretical HRO principles into clinical and administrative practice, furthering the pursuit of HRO in health care and achieving the aim of delivering safe, high-quality care.…”
mentioning
confidence: 99%
“…43 Many other studies have also identified the need for high quality education to improve AEFI reporting among HCPs. 43,44 The current study has shown a significant improvement in the knowledge of AEFIs and their reporting in the study population and could help to initiate and strengthen the reporting culture among the HCPs practicing at both private and public health care facilities. There would be a need for ongoing motivational communication to HCPs for AEFI reporting to maintain this at an optimum level.…”
Section: Outcome Of Educational Intervention On Safe and Quality Use Of Vaccinesmentioning
confidence: 78%
“…Dimana dari total 2.877 rumah sakit yang ada di Indonesia termasuk rumah sakit negeri maupun swasta hanya 334 rumah sakit yang melaporkan insiden keselamatan pasien (Daud, 2020). Kegagalan serta terlambatnya pelaporan insiden keselamatan pasien memiliki beberapa dampak serius jika tidak dijalankan dengan baik, dampak yang dapat ditimbulkan antara lain: terancamnya keselamatan pasien, pemberian perawatan serta pengobatan yang tidak tepat, serta dapat menimbulkan resiko kerugian terhadap rumah sakit (McFarland & Doucette, 2018).…”
Section: Pendahuluanunclassified